2016
DOI: 10.1117/12.2213423
|View full text |Cite
|
Sign up to set email alerts
|

Multi-kW coherent combining of fiber lasers seeded with pseudo random phase modulated light

Abstract: We report efficient coherent beam combining of five kilowatt-class fiber amplifiers with a diffractive optical element (DOE). Based on a master oscillator power amplifier (MOPA) configuration, the amplifiers were seeded with pseudo random phase modulated light. Each non-polarization maintaining fiber amplifier was optically path length matched and provides approximately 1.2 kW of near diffraction-limited output power (measured M 2 <1.1). Consequently, a low power sample of each laser was utilized for active li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Random phase modulation of a narrow band laser has been realized by applying a white noise generator to an external electro-optic phase modulator [3][4][5][6]. More recently, PRBS waveforms with π phase shifts have been extensively investigated for SBS mitigation [7,8]. A comprehensive theoretical study showed that "for a fiber length of length 9 m the patterns at or near 7 n = provide the best mitigation of SBS with suppression factors approaching 17 dB at a modulation frequency of 5 GHz" [9].…”
Section: Introductionmentioning
confidence: 99%
“…Random phase modulation of a narrow band laser has been realized by applying a white noise generator to an external electro-optic phase modulator [3][4][5][6]. More recently, PRBS waveforms with π phase shifts have been extensively investigated for SBS mitigation [7,8]. A comprehensive theoretical study showed that "for a fiber length of length 9 m the patterns at or near 7 n = provide the best mitigation of SBS with suppression factors approaching 17 dB at a modulation frequency of 5 GHz" [9].…”
Section: Introductionmentioning
confidence: 99%
“…The coherent synthesis efficiency of the experimental system is up to 99%, and the polarization extinction ratio of the output laser more than 29 dB. In 2016, Angel et al of U.S. Air Force Research Laboratory used the five polarization-controlled narrow linewidth based amplifiers achieved 5 kW output power [9]. The amplifier is based on pseudo-random phase modulation and takes a low power sample from the output of each laser and polarizes it with General Photonics polarization controller.…”
Section: Introductionmentioning
confidence: 99%
“…Then, a beam splitter is usually set in the optical path to sample the expanded laser array after they are emitted to the free space, namely the external phase sensing technique [24][25][26]. At last, some mature phase-locking techniques are applied to lock the phase, such as the dithering technique [27][28][29], the stochastic parallel gradient descent (SPGD) algorithm [30][31][32], interference measurement [18,33,34], and machine learning [35][36][37][38][39], etc. Despite that the external phase sensing technique has exhibited impressive performances for phase locking, further power scaling still faces challenges.…”
Section: Introductionmentioning
confidence: 99%